2019
DOI: 10.1111/csp2.6
|View full text |Cite
|
Sign up to set email alerts
|

Managers' perceptions of protected area outcomes in Madagascar highlight the need for species monitoring and knowledge transfer

Abstract: Considerable effort has gone into assessing the effectiveness of protected areas (PAs) in preventing biodiversity loss, and PA impacts on local communities. However, little is known about how pressures are being perceived and dealt with by local PA managers and what perceptions managers have of biodiversity trends and human-induced pressures in the PAs they manage. We surveyed and convened a workshop with PA managers in Madagascar asking about the impacts of PA establishment. The managers reported that PAs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Our results are somewhat in line with previous research: the few studies that have looked at correlations between management inputs and PA impacts in avoiding forest loss have reported no or weak links Nolte & Agrawal, 2013;Schleicher, Peres, & Leader-Williams, 2019). It may be that the observed patterns correspond with reality, and that there is a true disconnect between PA management actions and effectiveness, and that other factors, such as wider governance quality, are more important in determining PA performance (Eklund & Cabeza, 2017;Pyhälä, Eklund, McBride, Rakotoarijaona, & Cabeza, 2019;Schleicher et al, 2019). However, we identify at least three further alternative interpretations that could help to explain the lack of statistical association between levels of management and avoided deforestation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are somewhat in line with previous research: the few studies that have looked at correlations between management inputs and PA impacts in avoiding forest loss have reported no or weak links Nolte & Agrawal, 2013;Schleicher, Peres, & Leader-Williams, 2019). It may be that the observed patterns correspond with reality, and that there is a true disconnect between PA management actions and effectiveness, and that other factors, such as wider governance quality, are more important in determining PA performance (Eklund & Cabeza, 2017;Pyhälä, Eklund, McBride, Rakotoarijaona, & Cabeza, 2019;Schleicher et al, 2019). However, we identify at least three further alternative interpretations that could help to explain the lack of statistical association between levels of management and avoided deforestation.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the PAME data ignores aspects related to the wider quality of governance, such as for example law enforcement and corruption (Eklund & Cabeza, 2017). Previous studies have shown that PA managers often report such issues as being main obstacles for carrying out effective management (Pyhälä et al, 2019;Schleicher et al, 2019), as the mandate of a local manager is quite limited in the face of such powerful drivers.…”
Section: Caveatsmentioning
confidence: 99%
“…It is therefore apparent that, given the actual and potential valuable role of PAs in fostering biodiversity conservation, understanding whether and why PAs are achieving success is essential to maintain, or improve, the way PAs are managed by investigating the relationship between management actions and biodiversity condition (Timko and Innes, 2009;Pyhälä et al, 2019). However, only limited attempts have been made in Ethiopia to regularly evaluate the status and threats of the PAs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the analysis of how management interventions relate to PA outcomes (Carranza et al, 2014). On the other hand, most PAs lack resources (expertise, finance and/or time) to collect intensive field-based ecological data needed to relate management interventions to threat level and/or to state of biodiversity (that is, to evaluate the effectiveness of past and present management interventions made in reducing the threats and their impacts) (Asefa et al, 2015;Pyhälä et al, 2019). To overcome such limitations, in this study we used "The Theory of Change Model" tool to assess severity of threat factors in five PAs of Ethiopia and to explore potential management interventions required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation